Mediation as a means of conflict resolution in a student environment (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the study of such a social categoryas mediation. The relevance of introducing such a procedure in thestudent community is proved, since the unification of different personalitiescan become the basis for the development of conflicts. The results of apsychological and pedagogical experiment in two age groups are described:first-year students of various higher educational institutions. It is shownthat more often, depending on the age group, students choose a strategyfor behavior in a conflict situation as rivalry and cooperation, and theolder age group is also a compromise. It is proved that mediation is mosteffective for resolving conflicts in the student community.
Keywords: сonflict; pedagogical experiment; mediation; mediation procedure; reconciliation; conflict resolution; student environment